2019
DOI: 10.1016/s2214-109x(19)30360-2
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic heart disease burden, trends, and inequalities in the Americas, 1990–2017: a population-based study

Abstract: Background The World Health Assembly 2018 approved a resolution on rheumatic heart disease to strengthen programmes in countries where this condition remains a substantial public health problem. We aimed to describe the regional burden, trends, and inequalities of rheumatic heart disease in the Americas. MethodsIn this secondary analysis of the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2017, we extracted data for deaths, prevalence of cases, disability-adjusted life-years (DALYs), years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 28 publications
1
55
0
3
Order By: Relevance
“…The most poignant story in these data is that of those left behind. Here, Ordunez and colleagues 2 Other examples of the association between rheumatic heart disease and economic prosperity exist. In the USA, the incidence of acute rheumatic fever declined dramatically with socioeconomic development, even before the arrival of penicillin for primary rheumatic fever prevention.…”
Section: Rheumatic Heart Disease and Socioeconomic Developmentmentioning
confidence: 99%
“…The most poignant story in these data is that of those left behind. Here, Ordunez and colleagues 2 Other examples of the association between rheumatic heart disease and economic prosperity exist. In the USA, the incidence of acute rheumatic fever declined dramatically with socioeconomic development, even before the arrival of penicillin for primary rheumatic fever prevention.…”
Section: Rheumatic Heart Disease and Socioeconomic Developmentmentioning
confidence: 99%
“…In this report they estimated age-adjusted incidence, mortality and DALYS in 37 counties throughout South America. In spite of the considerable drop in both incidence and mortality during the period of the study (1990-2017), there were marked regional inequalities related mainly to socioeconomic factors and facilities for RHD prevention and control (4). A particular problem in the estimation of the true burden of the disease is the use of surveys of schoolchildren in many population studies.…”
Section: Global Databasesmentioning
confidence: 99%
“…It is the most common cause of progressive acquired heart disease in children and young adults (2,3). Although once common throughout the world, the disease burden is now almost entirely limited to low and middle income countries and the poor indigenous populations of some wealthy countries (3)(4)(5). RHD continues to be an important cause of mortality and disability and yet remains a neglected disease (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…RHD has been eradicated/controlled in developed countries, whereas it remains a major health concern in developing countries like Pakistan. The prevalence of RHD is estimated to be much higher in developing countries, 3 about 24/1000 versus just 0.3/1000 in industrialised nations. 4 S F Rizvi et al found prevalence of 5.7/1000 in rural population of district of Rahim Yar Khan in Pakistan.…”
Section: Introductionmentioning
confidence: 99%